Effect of Hydroxypropyl Methylcellulose–Lipid Edible Composite Coatings on Plum(cv.Autumn giant) Quality During Storage - Pérez-Gago, María B.; Rojas-Argudo, Cristina; Del-Río, Miguel A. (Wiley, 2023)
‘Autumn Giant’ plums were coated with edible hydroxypropyl methylcellulose-lipid composite coatings. The coatings consisted of beeswax or shellac, at 2 lipid content levels (20% and 60% dry basis). Weight loss of coated plums decreased as lipid content increased. No differences on weight loss were observed between uncoated and 20% lipid-coated plums, indicating that the natural waxes of plums are as effective as coatings having 20% lipid. Water-dipped plums experienced the highest weight loss. Fruit texture was not affected by coating after short-term storage at 20 °C. However, for prolonged storage at 20 °C, the coatings significantly reduced texture loss and internal breakdown compared to uncoated and water-dipped plums.